Development of a pressure sensor platform for direct measurement of Head Injury Criterion (HIC) - Krzeminski, D. E.; Fuss, F. K.; Weizman, Y.; Ketabi, A.; Piland, S. G. (Procedia Engineering, 2015)
Existing helmet sensor technologies are cost prohibitive or limited in capability to comprehensively assess sports-related head injury. Therefore, development of an accurate, fully compatible low-cost pressure-sensitive sensor is warranted. The aim was to develop a piezo-resistive sensor platform for direct measurement of HIC. Using a programmable microcontroller and 30x35 mm sensor, fifty drop tests with a 5 kg mass were conducted using a Kistler force plate with maximum vertical force of 5000 N. The Power function correlation between force-plate-derived peak force and sensor-derived peak resistance was high (r^2 = 0.974) and used to calculate sensor-derived force-time data. Analysis of force-time curves yielded comparable peak forces (R = 0.982) and time to peak forces (R = 0.938), yet sensor-derived impact durations were elevated (R = 0.498). High linear correlation was found between force-plate- and sensor-derived HIC (r^2 = 0.974). The force plate-derived HIC can be directly estimated with sufficient accuracy from sensor-derived force (r^2 = 0.980) and a residual standard deviation of 11% at HIC >100. Overall, results substantiated the piezo-resistive sensor platform for direct HIC measurement and development of a full-scale helmet system.